2021
DOI: 10.1108/ramj-08-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Sharing economy services in Dhaka: a change towards women’s perception of commuting

Abstract: Purpose In the modern era of transportation, using a ride-sharing service can add an extra value to the lifestyles of women. Also, women are thinking about the ride-sharing service, what are the factors they consider while purchasing the service and so on. The purpose of this study is to find out women’s perception of ride-sharing services. Design/methodology/approach This paper is based on deductive research approach and descriptive research design. This paper has followed mixed research method by using qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Research has shown that perceived convenience significantly influences consumers' intention to use ride-sharing services (Fu et al, 2022). Elements such as easy payment systems and the ability to track journeys and transactions enhance the convenience of ride-sharing services (Hoque & Saumi, 2021). The convenience offered by ride-sharing services is also a key factor in providing flexible and efficient urban transportation solutions, especially during peak hours when traditional taxi services are insufficient (Albishari et al, 2023).…”
Section: Perceived Conveniencementioning
confidence: 99%
“…Research has shown that perceived convenience significantly influences consumers' intention to use ride-sharing services (Fu et al, 2022). Elements such as easy payment systems and the ability to track journeys and transactions enhance the convenience of ride-sharing services (Hoque & Saumi, 2021). The convenience offered by ride-sharing services is also a key factor in providing flexible and efficient urban transportation solutions, especially during peak hours when traditional taxi services are insufficient (Albishari et al, 2023).…”
Section: Perceived Conveniencementioning
confidence: 99%
“…In Dhaka, harassment of women on public transport is fairly widespread. Ride-sharing businesses strive to provide excellent service, which benefits both drivers and passengers (Hoque & Saumi, 2021). The chi-square test was used for both groups of students to determine the effect of shared mobility services on their mode choice.…”
Section: The Consequences Of Ride-sharing Services On the Female Stud...mentioning
confidence: 99%
“…Among these, the structural dimension refers to the ability of individuals to establish contact with others and gain advantages from social interactions; the relational dimension is the degree of mutual trust and reciprocity among individuals; the cognitive dimension is the embodiment of common interests, values, and expressions among individuals in information exchanges. Because the social capital acquired by individuals in real or virtual worlds can reflect the characteristics of their social relations, reputations, and abilities, the theory of social capital is widely used in research on word-of-mouth and trust relationships [1,[18][19][20][21][22][23][24].…”
Section: Social Capital Theorymentioning
confidence: 99%